MANUAL THERAPY AS AN ALTERNATIVE TREATMENT FOR PANIC ATTACKS (World Science, 2019)
In worldwide medical practice panic attacks are treated mainly by psychological methods and medication. Cognitive-behavioral therapy combined with selective serotonin reuptake inhibitors is considered to be the most effective method of their treatment. However, it has been proven that about a third of patients with panic attacks are treatment resistant. Such people continue experiencing panic attacks and various other symptoms of panic disorder even after receiving the aforementioned treatment. It is this group of patients who are being targeted by the proposed research – manual therapy as an alternative treatment for panic attacks.